2012
DOI: 10.1371/journal.pone.0034915
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Maternal CTCF Is Associated with Peri-Implantation Lethality of Ctcf Null Embryos

Abstract: CTCF is a highly conserved, multifunctional zinc finger protein involved in critical aspects of gene regulation including transcription regulation, chromatin insulation, genomic imprinting, X-chromosome inactivation, and higher order chromatin organization. Such multifunctional properties of CTCF suggest an essential role in development. Indeed, a previous report on maternal depletion of CTCF suggested that CTCF is essential for pre-implantation development. To distinguish between the effects of maternal and z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
110
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 52 publications
2
110
2
Order By: Relevance
“…This observation is in agreement with data from COS-1 cells, in which Hmgb2 knockdown suppresses cell division (46). Furthermore, the cell type-specific lethality of Ctcf levels is also in agreement with data showing that Ctcf knockout is embryonic lethal in mice (47,48). Ctcf depletion in isolated cells often affects cell division or cell death processes, but in a cell type-dependent manner, potentially due to the cell type-specific localization of Ctcf and arrangement of a higher order structure coordinated by the protein (49).…”
supporting
confidence: 91%
“…This observation is in agreement with data from COS-1 cells, in which Hmgb2 knockdown suppresses cell division (46). Furthermore, the cell type-specific lethality of Ctcf levels is also in agreement with data showing that Ctcf knockout is embryonic lethal in mice (47,48). Ctcf depletion in isolated cells often affects cell division or cell death processes, but in a cell type-dependent manner, potentially due to the cell type-specific localization of Ctcf and arrangement of a higher order structure coordinated by the protein (49).…”
supporting
confidence: 91%
“…These findings, however, refer to the mouse developing limb and do not rule out a role of CTCF during early embryogenesis when the proposed kernel is active. In line with this idea, a recent report demonstrated that CTCF knockout mice die after the blastocyst stage (33). Fourth, animals that display Hox gene clustering should possess CTCF, and vice versa.…”
Section: Conservation Of Ctcf Sites In Vertebrate and Drosophila Hoxmentioning
confidence: 83%
“…CTCF may activate or derepress transcription in oocytes, and its depletion can induce mitotic defects and apoptosis [24]. Moreover, in the presence of maternal CTCF, zygotic CTCF expression does not CTCF ROLE IN EPIGENETICS, REPRODUCTION AND ARTS seem to be required for preimplantation mouse embryo development, and the loss of maternal transcripts is associated with apoptosis in the developing embryo and peri-implantation lethality [79]. During mouse ESC differentiation, unmethylated CpG islands showed reduced nucleosome occupancy and enrichment in CTCF-binding sites [80].…”
Section: Ctcf Gametogenesis and Embryo Developmentmentioning
confidence: 99%